Analysis of Optimization Waena Terminal Infrastructure, Jayapura City - Rante, Harmonis (Formosa Journal of Science and Technology, 2024)
A terminal is a part of land transportation which is the node point for various land transportation facilities (modes). The Waena Terminal has been equipped with terminal facilities and complementary buildings, but has not been used optimally, and even looks dirty and unkempt. This research aims to analyze the condition of the infrastructure, utilization and maintenance of the Waena Terminal. This research was conducted in Jayapura City, precisely at the Waena Public Transport Terminal which is administratively part of the Jayapura Municipal government area. Data analysis was carried out qualitatively. The research results show that the physical infrastructure at Waena Terminal is very complete when viewed against the standards set by the government. However, in terms of soft infrastructure, the Waena terminal has not been fulfilled, namely there is no terminal management by the related parties. The use and maintenance of the Waena Terminal has not gone well because it appears there is no terminal management.